Experimental study on polymer friction composite with natural friction modifiers for brake pads - Mitali Gore; Ajit Bhosale; Mithul Naidu; Robert Cep; Sachin Salunkhe; Emad Abouel Nasr (PLoS ONE, 2025)
The increasing concern over environmental pollution from brake dust and the adverse impacts of conventional brake pad materials, such as metallic, semi-metallic, and ceramic composites, has prompted the exploration of more sustainable alternatives. Traditional brake pads release harmful non-exhaust emissions that contribute to air pollution and wear down quickly, posing both environmental and operational challenges. This study investigates the development and performance evaluation of polymer friction composites enhanced with natural friction modifiers sourced from agricultural waste materials like walnut shell, coconut shell, and groundnut shell powders. These materials were selected for their biodegradability, lightweight properties, and cost-effectiveness. Three types of polymer reinforced composites—WPRC (Walnut Powder Reinforced Composite), CNPRC (Coconut Shell Powder Reinforced Composite), and GNPRC (Groundnut Shell Powder Reinforced Composite)—were manufactured according to ASTM G99 standards. A pin-on-disc tribometer or an L27 Taguchi experimental setup were used to measure friction and wear. The tests showed that WPRC had the best general performance of all the composites that were tried. It had stable coefficients of friction and a low specific wear rate. The results indicate that natural friction modifiers could improve the environmental and operational performance of polymer composites, by replacing existing brake pad materials with a more environmentally friendly alternative.